Parâmetros de estresse oxidativo em jundiás (Rhamdia quelen) expostos a formulações comerciais contendo glifosato e clomazone - Menezes, Charlene Cavalheiro de (2010)
The use of herbicides has increased in agriculture and pisciculture for controlling plant weeds, but the indiscriminate use can cause contamination to organisms such as fish. Therefore, the aim of this study was to evaluate the effects to commercial formulations of glyphosate and clomazone affects oxidative stress parameters in silver catfish (Rhamdia quelen). Silver catfish were exposed to: 0 (control), 0.45 or 0.95 mg/L of glyphosate (480 g/L) and 0 (control), 0.45 or 0.91 mg/L of clomazone for eight days and after transferred to water without the herbicide to equal period. The parameters analyzed were lipid peroxidation estimated by a TBARS levels (thiobarbituric acid reactive species), protein carbonyl and the antioxidants activity such as catalase (CAT), superoxide dismutase (SOD), glutathione S-transferase (GST), ascorbic acid and non-protein thiols. The results showed that fish exposed to glyphosate presented increased of TBARS levels in liver and muscle at the higher concentration, whereas in brain this increase was observed in the two concentrations used. When exposed to clomazone caused an enhanced in TBARS levels in muscle at both concentrations, in liver in the higher concentration, while in the brain showed no alterations. The protein carbonyl increased in the liver of silver catfish after exposure to both concentrations of two herbicides. In silver catfish exposed to glyphosate activities of CAT and SOD did not change, while GST reduced at the concentrations of 0.45 and 0.95 mg/L. The ascorbic acid levels in the liver did not change after exposure to the herbicide and the non-protein thiols levels reduced the concentration of 0.95 mg/L. In fish exposed to clomazone the CAT activity did not change and the SOD increased in the liver at the concentration 0.91 mg/L. The GST activity, ascorbic acid and non-protein thiols increased in the liver at the concentrations of 0.45 and 0.91 mg/L. In the recovery period most of the altered parameters recovered to both herbicides, after eight days in water without herbicide, except for the GST enzyme and ascorbic acid levels after exposure to clomazone. The results obtained in this study may suggest that in a short period of time the herbicides glyphosate and clomazone are able of inducing oxidative stress in the silver catfish, being these changes transient and reversible.